Design of a stator for a high-speed turbo-generator with fixed permanent magnet rotor radius and volt-ampere constraints - Fernando, Nuwantha; Arumugam, Puvaneswaran; Gerada, C. (IEEE, 2018)
This paper investigates high-speed surface PM machine design for portable turbo-generator applications. The rotor radius is fixed to achieve certain optimal characteristics of the magnet retention mechanism. The basis of this paper is to design and select the stator. The stator designs are populated by different slot/pole combinations, winding arrangements and over a range of possible stack lengths. However, the design is constrained by physical diameter, stack length and electrical volt-ampere constraints. A large number of preliminary machine designs do not satisfy the specified turbo-generator torque/speed requirements under the given volt-ampere constraints and therefore it is ineffective to perform Finite Element analysis on all preliminary design variations. In order to establish the feasibility of a machine design to fulfill the specified turbo-generator torque/speed requirements, the concept of inductance-limits is presented and then linked with stator design parameters. By application of this analysis strategy, a confined optimal set of stator designs are obtained and are subjected to detailed finite element simulations. A final machine design is selected and fabricated. Experimental results are presented for the validation of the final machine design.